Effect of some plant extracts on controlling sugar beet damping-off and root rot diseases casued by Rhizoctonia Solani KUHN. - Gouda M.l. (2007)
In vitro, The effect of six plant originated extracts had been studied on reducing the linear growth of Rhizoctonia solani Kuhn,the causal pathogen of damping-off and root rot disease of sugar beet plants. Under greenhouse and field conditions, the effect of improving the number of survived seedling and root rot was also studied. Extracts of Ammi visnaga (Picktooth) (seeds), Boughainvillae spectabilisWilld.(Boughainvillia) were superior than the other materials in reducing the pre-and post emergence damping-off and root rot of sugar beet as well as the disease severity.The rest materials were less effective in decreasing the disease incidince. At the same time, increasing the concentration of the tested materials significantly reduced the linear growth of R. solani. However, the fungicide Rizolex T. 50 was more effective than plant the extracts. Plant extracts were more effective and increased morpholigical characters, plant hieght and Leaf area per plant, also increasing the yield compenents, total soluble solids (TSS), sucrose percent in root and sugar purity. Chemical components within seeds of A. visnaga were fractinated into three fractions.These fractions in addition to Khellin (active component in seeds) showed that fraction (3) and Khellin were the only ones which have the capability to check the fungal growth of the pathogen, also visnagin and Khellin are the chemical components responsible for inhibatory effect of seeds of A. visnaga against sugar beet infecting fungi. The fungicide Rizolex T.50 was used for comparative studies in controlling these diseases.
Includes reference.
Summary in Arabic.
1
Keywords: Sugar beet -- Diseases and pests; Root rots; Rhizoctonia solani